Frequência, preditores clínicos e significado prognóstico da doença arterial coronariana angiográfica em candidatos ao transplante renal - Seixas, Emerson de Albuquerque [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Introduction: cardiovascular diseases are major causes of mortality in chronic renal failure patients before and after renal transplantation. Among them, coronary disease presents a special emphasis. Predictors of risk for coronary artery disease has been used for its diagnosis. Few studies have validated clinical predictors to selection patients for invasive procedures for the diagnosis of coronary artery disease (CAD) before renal transplantation. Objective: this study evaluated the frequency and discriminatory power of clinical predictors of coronary artery disease in chronic renal failure patients undergoing dialysis who were renal transplant candidates, assessed a previously developed scoring system (Gowdak et al.) for coronary artery disease, and we also checked the association between coronary artery disease and outcomes of the study group. Methods: coronary angiographies conducted between March 2008 and April 2013 from candidates for renal transplantation from two transplant centers in São Paulo state were analyzed. Cross-sectional study was conducted to verify the predictive power of clinical parameters for the presence of significant coronary artery disease (≥70% stenosis in one or more epicardial artery or ≥ 50% in the left main coronary artery). In addition, the discriminating power of a previously established clinical risk score was assessed (which takes account of diabetes mellitus (DM), age and clinical manifestations of cardiovascular disease). It was also conducted observational longitudinal study and drew up survival curves according to the angiographic diagnosis to verify the association between the presence of coronary heart disease and outcomes. Results: we screened 128 patients, of which 23 were excluded. The prevalence of coronary atheromatosis of any grade was 60/105 (57%) and significant coronary atheromatosis was 30/105 (29%) in the total sample. The remaining 105 patients underwent coronary angiography, two were excluded because of recording outcomes failures, so 103 were included in the longitudinal analysis. Of the 105 patients, in six, the analysis of clinical data showed incomplete. These were excluded from the cross-sectional study that was conducted with 99 patients. Univariate logistic regression analysis identified the presence of DM, angina and / or previous infarction, clinical peripheral artery disease and hyperlipidemia as predictors of CAD. Multiple logistic regression identified only diabetes and angina and / or previous infarction as independent predictors. The previously developed scoring system showed a close association with the diagnosis of CAD, which validates its use in the patients studied. Mortality was lower than expected among patients on dialysis. The presence of CAD was associated with cardiovascular events and was not a predictor of mortality. Conclusion: the CAD was frequent in renal failure patients on dialysis candidates to kidney transplantation, can be identified by clinical data and identification by angiography can predict cardiovascular events.

Introdução: as doenças cardiovasculares representam a maior causa de mortalidade nos pacientes renais crônicos antes e após o transplante renal, dentre elas a doença coronariana apresenta destaque especial. Preditores de risco tem sido usados no seu diagnóstico que é desafiador. Poucos trabalhos validaram preditores clínicos de seleção para exames invasivos para o diagnóstico de doença arterial coronariana (DAC) antes do transplante renal. Objetivo: avaliar a frequência e poder discriminatório de preditores clínicos da presença da doença arterial coronariana em pacientes renais crônicos em programa de diálise candidatos ao transplante renal, avaliar a performance da fórmula de Gowdak e colaboradores de risco de doença arterial coronariana e verificar a associação entre doença arterial coronariana e desfechos no grupo estudado. Métodos: foram analisadas as cinecoronariografias de candidatos ao transplante renal de dois centros de transplante renal do estado de São Paulo, realizadas entre março de 2008 e abril de 2013. Foi realizado estudo transversal para verificar o poder preditivo de parâmetros clínicos para a presença de doença coronária significativa (estenose ≥70% em uma ou mais artérias epicárdicas ou ≥ 50% no tronco da coronária esquerda). Adicionalmente, verificou-se o poder discriminatório de um escore clínico de risco previamente estabelecido (que leva em conta presença de diabetes melito (DM), idade e manifestações clínicas de doença cardiovascular). Foi realizado também estudo longitudinal observacional e traçaram-se curvas de sobrevida de acordo com o diagnóstico angiográfico para verificar a associação entre a presença de doença coronária e desfechos. Resultados: foram rastreados 128 pacientes, dos quais, 23 foram excluídos. A prevalência de ateromatose coronária de qualquer grau foi de 60/105 (57%) e ateromatose coronária significativa foi de 30/105 (29%) no total da casuística. Os 105 pacientes restantes realizaram coronariografia, dois foram excluídos por falha de registro dos desfechos, portanto 103 foram incluídos em análise longitudinal. Dos 105 pacientes, em seis, a análise dos dados clínicos se mostrou incompleta. Estes foram excluídos do estudo transversal que foi realizado com 99 pacientes. Análise de regressão logística univariada identificou presença de DM, angina e/ou infarto prévio, clínica de doença arterial periférica e dislipidemia como preditores de DAC. Regressão logística múltipla identificou apenas diabetes e angina e/ou infarto prévio como preditores independentes. O escore clínico previamente desenvolvido apresentou associação estreita com o diagnóstico de DAC, o que valida seu uso nos pacientes estudados. A mortalidade foi menor do que à esperada entre os pacientes em diálise. A presença de DAC foi associada à ocorrência de eventos cardiovasculares, porém não se associou à mortalidade. Conclusão: a DAC foi frequente em pacientes renais crônicos em programa de diálise candidatos ao transplante renal, pode ser identificada por dados clínicos e sua identificação por angiografia pode prever evento cardiovascular.
Frequency, clinical predictors, and prognostic significance of angiographic coronary artery disease in renal transplant candidates
Keywords: Chronic renal failure; Renal transplantation; Coronary artery disease; Coronary angiography; Insuficiência renal crônica; Doença coronariana; Transplante renal; Cinecoronariografia